A Common Model Is Essential for a Cumulative Science of Wisdom. Issue 2 (2nd April 2020) - Grossmann, Igor; Weststrate, Nic M.; Ferrari, Michel; Brienza, Justin P.
Abstract: We have introduced a common wisdom model to establish a shared language, clarify underlying theoretical assumptions, advance assessment tools, and foster evidence-based interventions for stimulating wisdom during challenging societal times. The common wisdom model synthesizes the views of numerous contemporary scientists working on wisdom and includes two components: perspectival meta-cognition and moral aspirations. Having received insightful commentaries on our model, here we consider the overall motivation for the model, address remaining jingle-jangle fallacies, clarify the meaning of morality for wisdom, and expand upon the relationship between moral and meta-cognitive components within the common wisdom model. We reflect on how the common wisdom model provides a nexus for integrating insights across multiple areas of research, affording plentiful opportunities for future research into wisdom's development, function, and underlying processes. We situate our reflections in the context of present-day pandemic-related uncertainties and unfolding societal shifts.